Intuition and Its Role in Ibn Sina'a Epistemology - Arif, Syamsuddin (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
Intuition and Its Role in Ibn Sina'a Epistemology